Chapter 11 Loneliness as Crisis in Britain after 1950 Temporality, Modernity and the Historical Gaze - Cooper, Fred (Taylor & Francis, 2023)
This chapter takes as its subject the framing of loneliness in post-war Britain as a distinctly modern crisis with a particular temporal resonance and urgency. It reflects on how time and temporality were central to newspaper discussions of loneliness as an urgent social problem in the late 1950s and early 1960s, produced by specific cultural, technological, ideological, and environmental contexts supposedly unique to mid-century modernity. Although predominantly a history of how loneliness was represented and thought of in post-war Britain, it is also a contemporary history of similar narratives of crisis, emergency, and epidemic in the twenty-first century; what these narratives mean for historical engagements with loneliness; and what historical engagements with loneliness mean for them.